2017
DOI: 10.1371/journal.pone.0177508
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Chinese natural bermudagrass [Cynodon dactylon (L.) Pers.] germplasm based on SRAP markers

Abstract: Bermudagrass [Cynodon dactylon (L.) Pers.], an important turfgrass used in public parks, home lawns, golf courses and sports fields, is widely distributed in China. In the present study, sequence-related amplified polymorphism (SRAP) markers were used to assess genetic diversity and population structure among 157 indigenous bermudagrass genotypes from 20 provinces in China. The application of 26 SRAP primer pairs produced 340 bands, of which 328 (96.58%) were polymorphic. The polymorphic information content (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 48 publications
5
28
1
Order By: Relevance
“…The average number of polymorphic bands is 13.6 per locus, a similar value (13.8) obtained by Zheng et al (2017) on Chinese bermudagrass (Cynodon dactylon) and this a little higher than the mean number of polymorphic loci reported for 152 studies of various plant species using SRAP (Robarts and Wolfe 2014), The moderate level of polymorphic loci (56%) obtained from this study suggesting that SRAP marker is considered reliable to detect polymorphism both at individual and population level. The values were generally lower than those obtained in other previous studies using more random markers such as RAPD, ISSR and SSR (Rout et al 2003;Bakshi and Sharma 2011;Cheng et al 2016;Zheng et al 2017). (Yulita and Rahmat 2019) considered SRAP and the other mentioned markers-e.g.…”
Section: Genetic Diversity Of Dalbergia Latifoliasupporting
confidence: 81%
See 2 more Smart Citations
“…The average number of polymorphic bands is 13.6 per locus, a similar value (13.8) obtained by Zheng et al (2017) on Chinese bermudagrass (Cynodon dactylon) and this a little higher than the mean number of polymorphic loci reported for 152 studies of various plant species using SRAP (Robarts and Wolfe 2014), The moderate level of polymorphic loci (56%) obtained from this study suggesting that SRAP marker is considered reliable to detect polymorphism both at individual and population level. The values were generally lower than those obtained in other previous studies using more random markers such as RAPD, ISSR and SSR (Rout et al 2003;Bakshi and Sharma 2011;Cheng et al 2016;Zheng et al 2017). (Yulita and Rahmat 2019) considered SRAP and the other mentioned markers-e.g.…”
Section: Genetic Diversity Of Dalbergia Latifoliasupporting
confidence: 81%
“…The scored data matrix was compiled in Excel software and used for further analyses. The polymorphic information content for each population and SRAP marker was following (Zheng et al 2017) a maximum of the value of Polymorphism Information Content (PIC) for dominant markers is 0.5 for f = 0.5 (Riek et al 2001). A cluster analysis was performed using UPGMA (Unweighted Pair Group Method with Arithmetic Average) (Sneath and Sokal 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The later one demonstrated that C. arcuatus separated from another seven species, and the species had different chromosome numbers clustered in all instances, indicating a close relationship between 2x and 4x [27]. Since then, more and more molecular markers have been used in genetic diversity analysis of Cynodon accessions, such as AFLP, ISSR, RAPD, SRAP and SSR (details in Table 3) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Khanal et al [44] successfully applied sugarcane EST-SSR analysing genetic diversity among triploid hybrids, tetraploid C. dactylon and diploid C. transvaalensis.…”
Section: Evaluation and Use Of Genetic Resourcesmentioning
confidence: 99%
“…This species is widely distributed in warm, humid and semi-arid areas around the Himalayas with excellent heat and drought tolerance capacity (Harlan et al 1970, Dunne et al 2019. This grass species is widely adapted to various environments of tropical and sub-tropical regions of the world and there are some ways for genetic diversity and population structure analysis of Bermudagrass (Zheng et al 2017). Bermuda grass has attracted interest of plant scientists because of their ease of cultivation, high forage production and high nutritional value (Pedreira 1996).…”
Section: Introductionmentioning
confidence: 99%